Analysis of Production Costs for White Oyster Mushroom (Pleurotus ostreatus) Cultivation at UMKM Agro Jamur Lombok, Kekeri Village, Gunungsari District, West Lombok Regency - Fadli, Fadli; Jupri, Ahmad; Maelia, Wina; Rozi, Tapaul; Hidayati, Lilik (Jurnal Biologi Tropis, 2025)
Indonesia with its tropical climate, boasts abundant agricultural potential, including on Lombok Island. UMKM Agro Jamur Lombok is a promising white oyster mushroom cultivation business in this region, driven by high market demand. This research aims to analyze the production cost structure and business feasibility of white oyster mushroom cultivation at UMKM Agro Jamur Lombok. The study employed a descriptive quantitative method, collecting data through observation, interviews, questionnaires, and literature reviews. Data analysis included calculations of production costs (fixed and variable), revenue, income, and business feasibility using the R/C ratio, B/C ratio, and Break-Even Point (BEP). The research results indicate that UMKM Agro Jamur Lombok's total production cost in 2024 was IDR 197,100,000, with a revenue of IDR 336,000,000, yielding an income of IDR 138,900,000. The feasibility analysis showed an R/C ratio of 1.7047 and a B/C ratio of 0.7047, indicating that the business is feasible and profitable. Although there was a decrease in production due to damaged grow bags, the R/C ratio (1.6536) and B/C ratio (0.6536) after the decline still demonstrate business viability. However, there is a discrepancy between the BEP selling price of grow bags (IDR 8,213/unit) and the actual selling price in the field (IDR 4,000/unit), which requires further review regarding cost efficiency or market dynamics.